Pieces of the Vanuatu Puzzle Archaeology of the North, South and Centre - Bedford, Stuart (Terra Australis, 2006)
Pieces of the Vanuatu Puzzle presents the results of the most intensive and widespread archaeological investigations in Vanuatu for more than 30 years. For the first time the results of extensive excavations carried out on three islands in the archipelago are published. The sites span from the period of initial Lapita settlement through to later cultural transformations. The research has brought greater clarity to the early history of the Vanuatu archipelago and has wider implications for the region in general particularly in terms of how processes of cultural change are explained. It is an essential reference work both for those archaeologists working in the western Pacific but also for those who deal with material culture generally and pottery more specifically.